2021
DOI: 10.22541/au.162392727.73465025/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What might COVID-19 Patients Experience after Recovery? A Systematic Review

Abstract: Objectives: To determine post-COVID-19 complications after recovery and investigate the reported cases of re-infection. Methods: The researchers systematically reviewed three databases: PubMed, Google Scholar, and Word Health Organization (WHO) COVID-19 database looking for studies reported post-COVID-19 complications and COVID-19 reinfection. The search was conducted between November 21, 2020 and January 14, 2021. Inclusion criteria were articles written in English and had primary data. The studies reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…It has been reported that long-haulers can have sequelae from one or more systems such as pulmonary, cardiovascular, gastrointestinal, renal, neural and musculoskeletal ( Leviner, 2021 ). Studies showed that regarding the musculoskeletal system sequelae, COVID-19 survivors, including those who also had the mild to moderate forms of the infection, can experience exacerbated muscle and joint pain ( Elhiny et al, 2021 ), and intense myalgia (muscle pain) ( Aiyegbusi et al, 2021 ; Carvalho-Schneider et al, 2021 ). Another sequel is intolerance to physical activities associated with a chronic fatigue condition and a difficulty in returning to a normal daily life ( Miyazato et al, 2020 ; Humphreys et al, 2021 ).…”
Section: Long-covid and Musculoskeletal Sequelaementioning
confidence: 99%
“…It has been reported that long-haulers can have sequelae from one or more systems such as pulmonary, cardiovascular, gastrointestinal, renal, neural and musculoskeletal ( Leviner, 2021 ). Studies showed that regarding the musculoskeletal system sequelae, COVID-19 survivors, including those who also had the mild to moderate forms of the infection, can experience exacerbated muscle and joint pain ( Elhiny et al, 2021 ), and intense myalgia (muscle pain) ( Aiyegbusi et al, 2021 ; Carvalho-Schneider et al, 2021 ). Another sequel is intolerance to physical activities associated with a chronic fatigue condition and a difficulty in returning to a normal daily life ( Miyazato et al, 2020 ; Humphreys et al, 2021 ).…”
Section: Long-covid and Musculoskeletal Sequelaementioning
confidence: 99%
“…6 Nine studies in China, Italy, Australia, and Germany have reported cardiovascular events of COVID-9. 3 The longest duration of follow-up documented among these studies was 3 months posthospital discharge. 7 The cardiovascular complications included an increase in heart rates, increase palpitations, elevation in blood pressure, chest tightness, pericardial chest pain, myocardial infarction, myocardial oedema, pericardial effusion, diastolic dysfunction, pulmonary hypertension and cardiac arrhythmia.…”
mentioning
confidence: 98%
“…Italy, the UK, Netherland, Canada, Saudi Arabia, Iran, France, Spain and the United States). 3 The commonly reported symptoms were breathlessness, lung function abnormalities, pulmonary fibrosis (interstitial thickening and crazy paving), residual ground-glass opacity, abnormal diffusion, pneumonia and pulmonary embolism. The longest duration of follow-up that reported respiratory sequelae was 4 months post-hospital discharge.…”
mentioning
confidence: 99%
See 2 more Smart Citations